Destination choices during internal temporary migration: Evidence from northern Bangladesh - Md. Sohel Rana; Amy Faye (University of Bonn, Center for Development Research (ZEF), 2024)
Whilst migration to urban areas is often understood through higher wage opportunities, it is not well understood why many rural poor often prefer rural destinations, particularly during temporary migration. This preference also calls for an investigation of the household-level income effects of different destination choices. Our study focuses on northern rural Bangladesh, where rural-bound temporary migration is common. We employ a multi-step conditional probit model with subsamples to analyze temporary migrant's destination choices, accounting for their self-selection into migration. Similarly, we apply a multi-step control function approach to address endogeneity in examining the income effects of different destination choices. Our results show that destination choices rely on migrants' individual characteristics, prior perceptions and subsequent experiences of the destination, and the influence of migrant networks. Although rural destinations often offer a better income-to-cost ratio, they are not necessarily better than urban destinations in increasing total household income. In fact, remittances from rural-bound temporary migration are lower than those from urban-bound migration. Yet, rural destinations offer greater utility maximization in the face of migrants' constraints, leading to a preference for this destination type among such migrants.
Keywords: J43; Q18; R23; 330; Agricultural lean periods; Bangladesh; Destination choices; Temporary migration; Rural-to-rural migration